Predictors of Retention in HIV Care among Youth (15–24) in a Universal Test-and-Treat Setting in Rural Kenya - Brown, Lillian B.; Ayieko, James; Mwangwa, Florence; Owaraganise, Asiphas; Kwarisiima, Dalsone; Bukusi, Elizabeth A.; Kamya, Moses R.; Petersen, Maya L.; Charlebois, Edwin D.; Havlir, Diane V. (Journal of acquired immune deficiency syndromes, 2017)
n 2013, 4 million youth age 15–24 years were living with HIV and 85% of HIV-infected youth live in sub-Saharan Africa1, where AIDS is the number-one cause of death of adolescents2. The magnitude of the HIV epidemic among youth in sub-Saharan Africa is expected to increase as demographic projections predict a “youth bulge”, increasing the population at risk for new infections, and leading to a doubling of the 15–24 year old HIV-infected cohort in sub-Saharan Africa by 20203. Retention in HIV care among this age group is essential to maximizing the benefits of antiretroviral therapy (ART), including improved quality of life, greater life expectancy, and prevention of new infections. Prior to guidelines for universal treatment, HIV-infected youth who started ART were more likely to be lost to follow-up4–6, report lower adherence4,6, and were more likely to have detectable viral loads than older age groups4,5,7. After two years of universal HIV testing and treatment in rural east Africa as part of the Sustainable East Africa Research in Community Health (SEARCH) trial, 82% of all adults with HIV in intervention communities were virally suppressed compared to only 67% of those age 15–248. These data suggest that even when high levels of viral suppression are achieved at the population level, current disparities could be exacerbated under universal treatment unless engagement in care among youth is specifically addressed. Understanding factors associated with retention in care, including any unique predictors, among this vulnerable age group will help develop additional interventions. We describe predictors of 12-month retention in HIV care among youth (15–24 years) who are linking to HIV care for the first time in rural Kenya as part of the ongoing SEARCH universal test-and-treat trial and compare these to young adults (25–29 years) and older adults (≥30 years).
Keywords: HIV/AIDS; sub-Saharan Africa; Retention in Care; Youth